2019
DOI: 10.1017/s0033291719003118
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing prisoners who think about suicide from those who attempt suicide

Abstract: Background Many people who consider suicide do not translate these intentions into action. Although prisoners constitute a particularly high-risk group for suicide, little is known about the factors that distinguish those who think about suicide from those who attempt suicide. Methods Participants were 1326 adult offenders (1203 men) randomly selected from 15 Belgian prisons, representing 14% of the national prison population. Multivariate regression analysis compared prisoners who attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 34 publications
(83 citation statements)
references
References 65 publications
(151 reference statements)
11
66
5
1
Order By: Relevance
“…Respondents were asked whether they had ever been told by a mental health professional, such as a psychiatrist or psychologist, that they had one or more of the following mental disorders: depressive disorder; bipolar disorder; psychotic disorder; posttraumatic stress disorder (PTSD); anxiety (e.g., panic) disorder; personality (e.g., antisocial or borderline) disorder; other mental disorders not listed. The wording of the question and choice of a self-report measure of lifetime psychiatric diagnoses is consistent with previous prison research (Binswanger et al, 2010;Favril & O'Connor, 2019).…”
Section: Clinical Variablessupporting
confidence: 71%
See 4 more Smart Citations
“…Respondents were asked whether they had ever been told by a mental health professional, such as a psychiatrist or psychologist, that they had one or more of the following mental disorders: depressive disorder; bipolar disorder; psychotic disorder; posttraumatic stress disorder (PTSD); anxiety (e.g., panic) disorder; personality (e.g., antisocial or borderline) disorder; other mental disorders not listed. The wording of the question and choice of a self-report measure of lifetime psychiatric diagnoses is consistent with previous prison research (Binswanger et al, 2010;Favril & O'Connor, 2019).…”
Section: Clinical Variablessupporting
confidence: 71%
“…However, our literature review identified only three studies adopting an ideation-to-action framework to discern risk of suicide in prisoners (see Table 1 for a summary). Results suggest that, relative to those who only think about suicide, prisoners who also attempt suicide are significantly more likely to report traumatic brain injury, non-suicidal self-injury, violent offending, indicators of childhood trauma, substance abuse, and certain mental disorders (Favril et al, 2020;Favril & O'Connor, 2019;Larney et al, 2012). These studies further indicate that approximately half (47-58%) of those who considered suicide had progressed to making a suicide attempt at some point.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations